2005
DOI: 10.1111/j.1525-1497.2005.40198.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in leisure-time, household, and work-related physical activity by race, ethnicity, and education

Abstract: Background: Racial and ethnic minority groups have lower levels of leisure‐time physical activity (LTPA) than whites, but it is unclear how much of this is explained by differences in socioeconomic status and health. Objective: To examine differences in LTPA, work‐related physical activity (WRPA; heavy household chores and strenuous job activities), and total physical activity (TPA) by race, ethnicity, and education. Design, Setting, and Participants: Cross‐sectional analyses of data from the 1992 Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
150
2
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(185 citation statements)
references
References 35 publications
19
150
2
14
Order By: Relevance
“…The demographic correlates of sport and physical activity participation were mostly consistent across the literature with the general trends suggesting that males participate in more leisure time physical activity than females [48][49][50]. There were a small number of studies, which did not find gender differences [36,39,51,52].…”
Section: Demographicsupporting
confidence: 72%
“…The demographic correlates of sport and physical activity participation were mostly consistent across the literature with the general trends suggesting that males participate in more leisure time physical activity than females [48][49][50]. There were a small number of studies, which did not find gender differences [36,39,51,52].…”
Section: Demographicsupporting
confidence: 72%
“…Given that demographics and past park use have been shown to influence perceptions of parks [33,64,65] as well as physical activity and health [29,[66][67][68][69][70], gender, age, income, race/ethnicity, and past park use were controlled for in the four models. To categorize past park use, respondents who indicated that they had not visited a park within the last month were treated as nonvisitors.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Physical activity rates decline dramatically as children grow from childhood to adolescence, a decline that continues with age and that holds true not just for Latinos but for the entire U.s. population. [10][11][12][13] because most Americans do not meet daily activity recommendations, policymakers have established goals to increase the number of people who lead active, healthy lives. 14,15 However, there are barriers to physical activity, such as unsafe neighborhoods and limited access to built environments.…”
Section: Introductionmentioning
confidence: 99%